2023
DOI: 10.3390/ijms24087017
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain and Extraterminal Domain (BET) Protein Inhibition Hinders Glioblastoma Progression by Inducing Autophagy-Dependent Differentiation

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive type of malignant primary brain tumor, and it is characterized by a high recurrence incidence and poor prognosis due to the presence of a highly heterogeneous mass of stem cells with self-renewal capacity and stemness maintenance ability. In recent years, the epigenetic landscape of GBM has been explored and many epigenetic alterations have been investigated. Among the investigated epigenetic abnormalities, the bromodomain and extra-terminal domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Upon combining genetic autophagy inhibition with JQ1, β3-tubulin and synaptophysin levels were lower than in the shRNA control samples. These results were confirmed with the pharmacological inhibition of autophagy using CQ, where the JQ1-induced accumulation of β3-tubulin and synaptophysin was suppressed upon CQ treatment, confirming the importance of the autophagic flux in JQ1-induced GBM differentiation [50].…”
Section: Glioblastomasupporting
confidence: 64%
See 4 more Smart Citations
“…Upon combining genetic autophagy inhibition with JQ1, β3-tubulin and synaptophysin levels were lower than in the shRNA control samples. These results were confirmed with the pharmacological inhibition of autophagy using CQ, where the JQ1-induced accumulation of β3-tubulin and synaptophysin was suppressed upon CQ treatment, confirming the importance of the autophagic flux in JQ1-induced GBM differentiation [50].…”
Section: Glioblastomasupporting
confidence: 64%
“…Colardo et al [ 50 ] studied the relationship between the BET family and autophagy in glioblastoma (GBM) using U87MG (U87), GL15 and the patient-derived GH2 cell lines. These investigators reported that the expression levels of BRD2 and BRD4 were high in these three cell lines, as well as in GBM patient samples.…”
Section: Autophagy and Bet Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations